Dental caries and social factors: impact on quality of life in Brazilian children - Milene Torres MARTINS; Fernanda SARDENBERG; Míriam Pimenta VALE; Saul Martins PAIVA; Isabela Almeida PORDEUS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objective of this study was to evaluate the impact of dental caries and social determinants in the Oral Health Related Quality of Life (OHRQoL) of children in Belo Horizonte, Brazil. This is a population-based cross-sectional study with a representative sample of 1,204 children aged 8 to 10 years randomly selected from 19 public and private schools. The children were clinically examined at school by two trained and calibrated examiners (Kappa = 0.78 - 1.00). The Decayed, Missing and Filled Teeth Index (DMF-T and dmf-t) was used for the diagnosis of dental caries. The social factors were determined by parents'/caregivers' schooling, household income, number of people in the household, type of school, and by the Social Vulnerability Index. The Brazilian version of the Child Perceptions Questionnaire for ages 8 to 10 years was used to assess the impact on quality of life. A total of 278 (23.1%) out of 1,204 children had at least one cavitated carious lesion and 47.0% presented a negative impact on OHRQoL. In the final multivariate Poisson's regression model, household income and presence of untreated dental caries were statistically associated with a negative impact on OHRQoL (p < 0.001).Children with dental caries and from low-income families had a higher negative impact on OHRQoL.